Nonpharmaceutical interventions reduce the incidence and mortality of COVID‐19: A study based on the survey from the International COVID‐19 Research Network (ICRN). Issue 2 (30th January 2023) - Park, Seung Hyun; Hong, Sung Hwi; Kim, Kwanghyun; Lee, Seung Won; Yon, Dong Keon; Jung, Sun Jae; Abdeen, Ziad; Ghayda, Ramy Abou; Ahmed, Mohamed Lemine Cheikh Brahim; Serouri, Abdulwahed Al; Al‐Herz, Waleed; Al‐Shamsi, Humaid O.; et al.
Abstract: The recently emerged novel coronavirus, "severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2), " caused a highly contagious disease called coronavirus disease 2019 (COVID‐19). It has severely damaged the world's most developed countries and has turned into a major threat for low‐ and middle‐income countries. Since its emergence in late 2019, medical interventions have been substantial, and most countries relied on public health measures collectively known as nonpharmaceutical interventions (NPIs). We aimed to centralize the accumulative knowledge of NPIs against COVID‐19 for each country under one worldwide consortium. International COVID‐19 Research Network collaborators developed a cross‐sectional online survey to assess the implications of NPIs and sanitary supply on the incidence and mortality of COVID‐19. The survey was conducted between January 1 and February 1, 2021, and participants from 92 countries/territories completed it. The association between NPIs, sanitation supplies, and incidence and mortality were examined by multivariate regression, with the log‐transformed value of population as an offset value. The majority of countries/territories applied several preventive strategies, including social distancing (100.0%), quarantine (100.0%), isolation (98.9%), and school closure (97.8%). Individual‐level preventive measures such as personal hygiene (100.0%) and wearing facial masks (94.6% at hospitals; 93.5% at mass transportation; 91.3% in mass gathering facilities) were also frequently applied. Quarantine at a designated place was negatively associated with incidence and mortality compared to home quarantine. Isolation at a designated place was also associated with reduced mortality compared to home isolation. Recommendations to use sanitizer for personal hygiene reduced incidence compared to the recommendation to use soap. Deprivation of masks was associated with increased incidence. Higher incidence and mortality were found in countries/territories with higher economic levels. Mask deprivation was pervasive regardless of economic level. NPIs against COVID‐19 such as using sanitizer, quarantine, and isolation can decrease the incidence and mortality of COVID‐19.